Development Dilemma: Understanding the Realm of Activity Based Learning in Professional Education (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Development Communication is described as the  systematic use of communication in support of national  development. The individuals who conceived  development communication/ journalism in 1960s  believed that there should be better trained and informed  economic specialists among the communicators. The  growth in the Third World is characterized by structural  inequalities and cleavages. The income gap between  rich and the poor is becoming wider. As a consequence,  the economic growth only contributes to the problem of  growing disparities, tendencies towards disintegration  and instability.Development Journalism is the need of the hour. By  concentrating on the development landmark the news  agencies can help Third World countries tackle their  problems of economic and social development, national  unity and stability and culture preservation.The remedy  neither lies in measures to restrict and control the  dissenting voices nor by strengthening their down  capacity to communicate by attempts to block or tear  down the capacities of others. A single standard of  control of communication systems throughout the world  will certainly prove counterproductive. For the worldwide  need is for more voices and not fewer.
Keywords: Professional Education; communication; national development; preservation